Class struggle in the era of post-politics - Abalo Ernesto; Jacobsson Diana (Nordicom Review)
This article addresses how class as a category of conflict and struggle is understood and shaped discursively in mainstream media today. We utilise a case study of how Swedish news media represents the long-lasting conflict in the Swedish labour market between the Swedish Dockworkers’ Union and the employer organisation, Sweden's Ports. Using critical discourse analysis, we show two ways in which class relations are recontextualised in three Swedish newspapers. One is through obscuring class and centring the conflict around business and nationalist discourses, which in the end legitimise a corporate perspective. The other, more marginalised, way is through the critique of class relations that appears in subjective discourse types. This handling of class, we argue, serves the reproduction of a post-political condition.